2021
DOI: 10.2174/1566524021666210202114844
|View full text |Cite
|
Sign up to set email alerts
|

Deeper Insight in Metastatic Cancer Progression; Epithelial-to- Mesenchymal Transition and Genomic Instability: Implications on Treatment Resistance

Abstract: : Therapy resistance remains the major obstacle to successful cancer treatment. Epithelial-to- mesenchymal transition [EMT], a cellular reprogramming process involved in embryogenesis and organ development and regulated by a number of transcriptional factors [EMT-TFs] such as ZEB1/2, is recognized for its role in tumor progression and metastasis. Recently, a growing body of evidence has implicated EMT in cancer therapy resistance but the actual mechanism that underlie this finding has remained elusive. For exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Genomic instability is a common feature in cancer with evidence of contribution of EMT (Nieto et al , 2016 ; Yang et al , 2020 ) and has frequently been observed in pre‐malignant mesenchymal cells in vitro as well as in tumors (Massague, 2012 ; Comaills et al , 2016 ; Caramel et al , 2018 ; Wang et al , 2019a ). Although EMT stimuli are normally anti‐proliferative, some cancer cells maintain cell doubling, perhaps at the expense of genome stability (Omabe et al , 2021 ). The involved mechanisms overriding the anti‐proliferative signals and the generation of genomic aberrations are poorly understood.…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic instability is a common feature in cancer with evidence of contribution of EMT (Nieto et al , 2016 ; Yang et al , 2020 ) and has frequently been observed in pre‐malignant mesenchymal cells in vitro as well as in tumors (Massague, 2012 ; Comaills et al , 2016 ; Caramel et al , 2018 ; Wang et al , 2019a ). Although EMT stimuli are normally anti‐proliferative, some cancer cells maintain cell doubling, perhaps at the expense of genome stability (Omabe et al , 2021 ). The involved mechanisms overriding the anti‐proliferative signals and the generation of genomic aberrations are poorly understood.…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
“…The involved mechanisms overriding the anti‐proliferative signals and the generation of genomic aberrations are poorly understood. Usually, DNA repair, cell cycle checkpoints, senescence and cell death in response to endogenous (e.g., during DNA replication) and exogenous DNA damages (e.g., during chemotherapy) are orchestrated by the DDR, which is a conserved, multifactorial and context‐dependent signaling network (Halazonetis et al , 2008 ; Omabe et al , 2021 ). Recent evidence suggests that EMT‐TFs differentially affect the DDR.…”
Section: Non‐classical Emt Featuresmentioning
confidence: 99%
“…In our in silico analyses, the KRAS mt / SMAD4 mt signature was associated with upregulation of the EMT phenotype and inflammatory responses. Data from multiple studies suggest an association of the EMT phenotype with radioresistance, where resistance to apoptosis and enhanced DNA damage repair capacity are often described as the underlying mechanism [ 20 , 21 , 22 , 23 ]. By contrast, the influence of enhanced inflammatory responses on cancer cell radiosensitivity is inconclusive because this phenotype can either positively or negatively influence anti-tumor immunity [ 24 ], and warrants further research.…”
Section: Discussionmentioning
confidence: 99%